Petrology and geochemical characteristics of amphibolite facies rocks in Xunyangba area, South Qinling Orogen, Central China - Kong, Juanjuan; Wang, Lei; Yao, Yongxiang; Lin, Jinyan; Xiao, Yuanyuan; Yang, Yiting (Frontiers in Earth Science, 2023)
As a tectonic block of the Qinling orogenic belt, central China, the South Qinling Orogen is generally believed to have a tight affinity with the Yangtze Block during Precambrian. The knowledge on the South Qinling Orogen is important to constrain tectonic evolution of the northern margin of the Yangtze Block basement. Previous studies mainly focused on the east segment of the South Qinling Orogen. This paper presented petrological, geochronological, and geochemical studies on the amphibolite facies rocks newly discovered in the middle section of the South Qinling Orogen. Geochemical studies indicate that the parental rock of these amphibolites is calc-alkaline island arc basalt, which was formed during the reconstruction of the Paleo-Middle Archean crust on the northern margin of the Yangtze Block 2362 ± 100 Ma ago (equivalent to metamorphic rocks of the Yudongzi Group). Later, these arc basalts experienced amphibolite facies metamorphism at 1500~1800 Ma, which is consistent with the metamorphism identified in the Yangtze Block, confirming the association of the South Qinling Orogen with the Yangtze Block basement. Subsequently, these amphibolite facies rocks further experienced three stages of metamorphism at c. 800 Ma, 440 Ma and 200 Ma in the context of northward subduction of the Yangtze Block.